Nipah virus infection: pathology and pathogenesis of an emerging paramyxoviral zoonosis. - Wong, K.T.; Shieh, Wun-Ju; Kumar, Shalini; Norain, Karim; Abdullah, Wahidah; Guarner, Jeannette; Goldsmith, Cynthia S.; Chua, Kaw Bing; Lam, Sai Kit; Tan, Chong Tin; Goh, Khean Jin; Chong, Heng Thay; et al. (2002)
In 1998, an outbreak of acute encephalitis with high mortality rates among pig handlers in Malaysia led to the discovery of a novel paramyxovirus named Nipah virus. A multidisciplinary investigation that included epidemiology, microbiology, molecular biology, and pathology was pivotal in the discovery of this new human infection. Clinical and autopsy findings were derived from a series of 32 fatal human cases of Nipah virus infection. Diagnosis was established in all cases by a combination of immunohistochemistry (IHC) and serology. Routine histological stains, IHC, and electron microscopy were used to examine autopsy tissues. The main histopathological findings included a systemic vasculitis with extensive thrombosis and parenchymal necrosis, particularly in the central nervous system. Endothelial cell damage, necrosis, and syncytial giant cell formation were seen in affected vessels. Characteristic viral inclusions were seen by light and electron microscopy. IHC analysis showed widespread presence of Nipah virus antigens in endothelial and smooth muscle cells of blood vessels. Abundant viral antigens were also seen in various parenchymal cells, particularly in neurons. Infection of endothelial cells and neurons as well as vasculitis and thrombosis seem to be critical to the pathogenesis of this new human disease.